Expressive, much? - Gutzmann, Daniel; Henderson, Robert (Proceedings of Sinn und Bedeutung, 2019)
This paper investigates a novel use of much in a construction that has not yet been recognized in the literature—Angry, much?—which we dub “expressive much”. Our primary proposal is that expressive much is a shunting operator in the sense of McCready 2010, which targets a gradable predicate and adds a speaker’s evaluative attitude about the degree to which an individual stands out on the relevant scale. In particular, we argue that it does so in a way that allows it to perform an “expressive question”, which can be understood as a counterpart to a polar question, but in the expressive meaning dimension.